Da'wah Communication Style with Games on Ustadz Abi Azkakia Through Live Tiktok - Khoirul Nasikhin; Sufyanto Sufyanto (Indonesian Journal of Cultural and Community Development, 2023)
This qualitative descriptive study aims to examine the communication style employed by Ustadz Abi Azkakia while utilizing the mobile game, Mobile Legends, for dawah (Islamic outreach) purposes on TikTok. By analyzing data gathered from live streaming sessions and video postings on his TikTok account, the author describes Ustadz Abi Azkakia's unique approach to dawah communication. The results reveal the utilization of two communication styles: assertive style (direct eye contact, humor, openness to opinions, expressive) and passive style (limited facial expressions, infrequent eye contact, gentle demeanor). This research sheds light on the innovative ways in which social media, particularly TikTok, can be employed for effective dawah communication, presenting opportunities for the wider Islamic community to engage and connect with a diverse audience. Highlights: The unconventional approach: Ustadz Abi Azkakia's use of Mobile Legends gaming on TikTok as a medium for dawah communication brings a fresh and unconventional perspective to Islamic outreach. Diverse communication styles: The study reveals the utilization of assertive and passive communication styles by Ustadz Abi Azkakia, showcasing the importance of adapting communication techniques to effectively engage with a diverse audience. The power of social media: This research highlights the potential of social media platforms, specifically TikTok, in enabling Islamic scholars to reach a wider and more diverse audience, fostering connections and promoting understanding in new and innovative ways. Keywords: Dawah communication, Ustadz Abi Azkakia, TikTok, Mobile Legends, Social media